Analisis Efektivitas dan Efisiensi Realisasi Belanja Daerah Kabupaten Jember Tahun 2021 2024 - Zefanya Risca Cristiani; Aura Aulia Sofia; Eva Hany Fanida; Ravienda Anita Fitrie (AKUNTANSI 45, 2026)
Optimal budget management is crucial to ensure regional development is on target amidst limited fiscal resources. This study aims to analyze the effectiveness and efficiency levels of regional expenditure realization in the Jember Regency Budget (APBD) for the 2021–2024 period. The method used is descriptive quantitative with document analysis of the Budget Realization Report (LRA) and literature study. Effectiveness is measured by comparing expenditure realization against its target, while efficiency is measured by comparing expenditure realization against revenue realization. The results show that the effectiveness level from 2021 to 2023 is in the effective category (91.68%–94.16%), but decreased to the moderately effective category (87.56%) in 2024. In terms of efficiency, expenditure realization in 2021 and 2022 fell into the inefficient category (104.66% and 112.06%), improved to less efficient in 2023 (96.08%), and showed optimal conditions in 2024. The implication of this research is the need to strengthen synchronization between expenditure planning and regional revenue capacity. Increasing efficiency is urgent to ensure financial management remains balanced and capable of supporting future regional fiscal sustainability.